Struktur Modal, Ukuran Perusahaan, dan Nilai Perusahaan: Studi Empiris pada Sub-Sektor Tekstil dan Garmen 2021-2023 - Yulia Wahyu Lestari; Purwanti Purwanti (Revenue: Lentera Bisnis Manajemen, 2026)
This research aims to analyze the influence of capital structure and company size on company value in the textile and garment sub-sector during the 2021-2023 period. The background to this research is the revival of the textile sector after the COVID-19 pandemic, which presents opportunities as well as challenges for companies to survive amidst business dynamics. The method used is a quantitative approach with secondary data from 12 textile and garment companies listed on the Indonesia Stock Exchange. The independent variables are capital structure and company size, while the dependent variable is company value which is measured using Price to Book Value (PBV). Data analysis uses panel data regression with the help of Eviews-12 software. The research results show that capital structure and company size have a significant influence on company value, with respective probability values ​​of 0.0006 and 0.0000. The coefficient of determination of 72.6% shows that the variability in company value can be explained by these two variables. An optimal capital structure helps a company minimize financial risks, while a larger company size provides a competitive advantage in the market. These findings emphasize the importance of strategic financial management in increasing company value. This research provides practical implications for corporate decision makers and stakeholders to maximize the performance of the textile and garment sector.